Systematic bioinformatics analysis identifies shikonin as a novel mTOR pathway inhibitor in triple-negative breast cancer progression - Liu, Wenna; Liu, Qingqing; Yao, Jingyue; Wu, Dan; Li, Wenxuan; Fu, Zhenkai; Zhao, Minggao; Liang, Ying (Frontiers in Pharmacology, 2025)
Triple-negative breast cancer (TNBC) remains a therapeutic challenge due to its resistance to conventional therapies and poor prognosis. Shikonin, a natural compound derived from Lithospermum erythrorhizon, has demonstrated antitumor potential in TNBC, though its molecular mechanisms remain unclear. In this study, shikonin’s antitumor effects were systematically evaluated using colony formation, wound-healing assays, transcriptomic profiling, and molecular docking. Results demonstrated that shikonin markedly inhibited TNBC cell proliferation and migration. Transcriptomic analysis identified downregulation of key mTOR signaling pathway genes (MTOR, CCND1, CDK6) post-treatment. Molecular docking confirmed direct binding between shikonin and the mTOR protein, suggesting mTOR pathway inhibition as a critical mechanism. Of note, the PI3K/AKT/mTOR axis is frequently hyperactivated in TNBC to regulate tumor proliferation and survival, yet existing mTOR inhibitors show limited efficacy in this subtype due to feedback activation of compensatory pathways and off - target effects that reduce their specificity for TNBC. Our findings highlight shikonin’s ability to target mTOR-related signaling, offering a novel strategy for TNBC treatment. This study provides foundational insights into shikonin’s molecular action, emphasizing its potential as a natural mTOR inhibitor tailored for TNBC. Further exploration of shikonin’s therapeutic applications could address the urgent need for targeted therapies against this aggressive breast cancer subtype, bridging gaps in current clinical approaches.